Mask communication: The development of the face covering as a semiotic resource through government public health posters in England and Wales. (December 2022) - Smith, Angela; Higgins, Michael
Abstract: This paper will explore the multi-modal semiotic properties of a selection of key public health information posters issued by the UK Westminster government on the use of masks and face coverings during the first year of the COVID-19 pandemic. Using multi-modal critical discourse analysis, we show how the posters featuring masks sustained consistent government-led branding, while drawing upon what we describe as "synthetic personalisation" to manage the orientation of the crisis as the pandemic progressed. Through this analysis, the article will highlight the possible contribution of these posters to an environment characterised by political confusion and enabling of a relatively widespread rejection of mask-wearing as a public health responsibility. Examining this within a broader decline in trust in government, we suggest the various attempts to produce a positive message about mask-wearing contributed instead to the appropriation of masks as symbols of individual alignment within a contested political field.